2006
DOI: 10.1017/s0031182006001533
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phylogenetic characterization of Cryptosporidium and Giardia from pigs and cattle in Denmark

Abstract: The genetic diversity of Cryptosporidium spp. and Giardia duodenalis from dairy cattle and pigs in Denmark was determined in the present study. Faecal samples from 1237 pigs and 1150 cattle originating from 50 sow herds and 50 dairy herds, respectively, were analysed for the presence of the two parasites by immunofluorescence microscopy. A large proportion of the (oo)cyst containing samples were selected for molecular characterization. Sequencing and phylogenetic analysis of the 18S rDNA locus and/or the HSP70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
138
9
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(186 citation statements)
references
References 49 publications
36
138
9
3
Order By: Relevance
“…Due to the frequent identification of Giardia cysts in faecal samples, cattle have long been considered an important source for human infections. Recent studies, however, indi- Table 1 The true prevalence of Giardia (%) (95% Probability Intervals in parentheses), for different age classes of dairy and beef calves (less than 4 weeks, 4-10 weeks and overall), together with the farm prevalence cated that cattle should not be considered as an important source for human giardiosis because most bovine cases of giardiosis are due to infection with G. duodenalis assemblage E (Hunt et al, 2000;O'Handley et al, 2000;Appelbee et al, 2003;Becher et al, 2004;Trout et al, 2004Trout et al, , 2005Trout et al, , 2006Langkjaer et al, 2007). Similarly, in the present study, the majority of the Giardia-positive samples were identified as G. duodenalis assemblage E based on the b-giardin gene, although a substantial number of the isolates from dairy calves were G. duodenalis assemblage A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the frequent identification of Giardia cysts in faecal samples, cattle have long been considered an important source for human infections. Recent studies, however, indi- Table 1 The true prevalence of Giardia (%) (95% Probability Intervals in parentheses), for different age classes of dairy and beef calves (less than 4 weeks, 4-10 weeks and overall), together with the farm prevalence cated that cattle should not be considered as an important source for human giardiosis because most bovine cases of giardiosis are due to infection with G. duodenalis assemblage E (Hunt et al, 2000;O'Handley et al, 2000;Appelbee et al, 2003;Becher et al, 2004;Trout et al, 2004Trout et al, , 2005Trout et al, , 2006Langkjaer et al, 2007). Similarly, in the present study, the majority of the Giardia-positive samples were identified as G. duodenalis assemblage E based on the b-giardin gene, although a substantial number of the isolates from dairy calves were G. duodenalis assemblage A.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, only a few molecular epidemiological studies have been conducted on calves. In Denmark, the majority of the isolates from cattle were identified as G. duodenalis assemblage E (Langkjaer et al, 2007). In contrast, a high prevalence of the zoonotic G. duodenalis assemblage A infections was reported in cattle in Italy (Berrilli et al, 2004;Lalle et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown previously that the occurrence of Cryptosporidium species in pigs is related to the stage of pig production. C. scrofarum was identified in post-weaned pigs and C. suis in suckling piglets (Langkjaer et al 2007, Suárez-Luengas et al 2007, Kváč et al 2009a, Němejc et al 2013. Although, in some of the studies, C. suis was detected in pigs at a different age, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…: +48 81 889 30 36 lowed by DNA sequence analysis allowed for identification of Cryptosporidium species and genotypes (Carreno et al 2001, Smith et al 2006). More recently, these methods have been widely used for detection and identification of Cryptosporidium isolates originating from pigs raised in Europe (Mišić et al 2003, Hajdusek et al 2004, Maddox-Hyttel et al 2006, Hamnes et al 2007, Langkjaer et al 2007, Suárez-Luengas et al 2007, Zintl et al 2007, Kváč et al 2009a, Asia (Chen and Huang 2007), North America (Jenkins et al 2010) and Australia (Ryan et al 2003, Johnson et al 2008). Despite differences observed in the extensiveness of the infection between swine herds, Cryptosporidium pig genotype II was predominantly detected.…”
Section: Introductionmentioning
confidence: 99%
“…DNA sequencing demonstrated that assemblage E was the most common genotype in Australia and the UK (Armson et al, 2009;Minetti et al, 2013), while in Canada assemblage B was predominant (Farzan et al, 2011). Assemblage A was found in both weaners and piglets in Denmark (Langkjaer et al, 2007) and in pigs in Australia (Armson et al, 2009). Unexpectedly, the canine-specific assemblages C and D and the feline-specific assemblage F were also found occasionally in pigs in different countries (Langkjaer et al, 2007;Armson et al, 2009;Minetti et al, 2013).…”
Section: Prevalence Of Giardia In Animalsmentioning
confidence: 97%